Experiences and Challenges of MTs Darussalam Teachers in Maintaining the Quality of Islamic Education Amidst Limited Supporting Facilities - Randi; Afni Fatimah; Intika Leosy; Aulia Putri Densi; Yoga Fajar Pratama (Journal of Islamic Pedagogy and Educational Development, 2026)
This research examines the lived experiences of teachers at MTs Darussalam in sustaining the quality of Islamic education despite the constraints of limited educational facilities. Islamic educational institutions are expected to integrate modern instructional practices with the cultivation of spiritual and moral values; however, insufficient resources frequently hinder teaching effectiveness and student learning outcomes. The objective of this study is to describe teachers’ experiences, identify the core challenges they encounter, and analyze the adaptive strategies they apply to uphold Islamic educational quality. A qualitative case study design was implemented, involving eight teachers selected through purposive sampling. Data were obtained through semi-structured interviews, classroom observations, and documentation of school programs, and were interpreted using thematic analysis. The findings highlight three major challenges: (1) a lack of adequate learning tools and digital media, (2) limited support for technological and digital literacy, and (3) restricted access to professional development opportunities. Nevertheless, teachers demonstrated resilience by (1) strengthening religious habituation programs, (2) adapting instructional approaches to the available facilities, and (3) fostering more intensive collaboration with parents and school committees. The study concludes that the teachers’ professional commitment and internalization of Islamic values play a crucial role in maintaining educational quality under resource-limited conditions. The results hold theoretical significance for the development of resilience models in Islamic education and offer practical recommendations for policymakers to enhance facility support and teacher training programs.